PENERAPAN SISTEM INFORMASI MANAJEMEN PENDIDIKAN DALAM PROSES PEMBELAJARAN DI SMP NEGERI 21 MAKASSAR - Ismail, La Ode; Sinen, Ristati (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This study aims to: 1). To know the implementation of management information system in SMP Negeri 21 Makassar. 2). To know the learning process at SMP Negeri 21 Makassar. 3). To know the factors that support the implementation of management information system in SMP Negeri 21 Makassar. This type of research is qualitative, with data acquisition through observation, interview, documentation. The validity of data in this study using triangulation. The results of this study include: (1). Implementation of Management Information System at SMP Negeri 21 Makassar has been done well. This is manifested in the use of data management applications dapodik and information technology in supporting the learning process by providing educational services based on infrastructure technology, such as learning facilities by combining computers with wifi. (2). Implementation of the learning process in SMP Negeri 21 Makassar is, before implementing the learning process must go through three stages namely, first, the planning stage, by making effective day analysis and analysis of learning programs, making annual programs, preparing syllabus, preparing lesson plans, and make assessment of learning. Second, the implementation phase, by analyzing aspects of the approach, aspects of strategy and tactics, aspects of methods and techniques. Learning media used are, print media (books), pictures, LCD and computer. Third, the evaluation stage of learning knowledge is tested in writing, oral, and a list of exam questions. Evaluation of skills learned evaluated with practice exams, and analysis of tasks evaluated by educators themselves. (3). Factors that support the existence of management information system that is the dapodik system containing data educators and data learners. So it can be concluded that the management information system is very supportive in the world of education, especially in the learning process at SMP Negeri 21 Makassar.